El desarrollo de las MiPymes Manabí post terremoto 16 a y su reactivación productiva a través del sector financiero popular y solidario en los periodos 2016 – 2018 - Mesías Pino, Manuel Francisco (2019)
The present titling work was carried out within the framework of knowing how the Popular and Solidarity Financial Sector contributed to the productive reactivation of the Manabí MSMEs after the 16 A earthquake the research was field, descriptive, documentary and correlational, for its development established, in the first phase the policies for productive reparation three phases were analyzed where it was known that the State created the Law of Citizenship Solidarity and Co-responsibility, so that the Financial Institutions would accept these and apply them, in the second phase the support received by the microentrepreneurs was identified, interviews were conducted with the managers and heads of agencies of the savings and credit cooperatives located in the cantons that had the greatest impact, on the other hand through the surveys it was possible to carry out a thorough check of the entrepreneurs verifying if these loans achieved economic activation, finally the development evaluation that the businesses have achieved for their productive reactivation, was defined by Pearson's correlation, allowing to measure variables of interest, and thus to conclude that through the policies destined to give grace periods, entrepreneurship credits, renovations and refinancing destined to the productive reactivation, where it was identified that the support by the SFPS in the cantons with the greatest impact was minimal , because a large part of the respondents could not access loans because they were not credit subjects, therefore the SFPS did not contribute greatly to the progress of the economic sectors of the province.